Inside the city : a guide to London as a financial centre - Clarke, William M. (London ; Boston : G. Allen & Unwin, 1979)
Inside the City looks at The City of London as one of the important financial centres in the world. The book provides an interesting insight into the City as a major centre of international banking, asking key questions such as, how long the city can last as a major centre, how do its services compare with other centres, and what it can do to maintain its present position? The book examines how the great network of markets and institutions that make up the City operated when the book was written, providing key chapters on the Stock Exchange, institutional and private investors, the banking world, including foreign and merchant banks, the commodity and money markets, Euromarkets, Sterling and insurance. This book will be of interest to those studying or researching in the field of economics and finance.
Includes bibliographical references and index.
rpm 25/04/2018
Loans
Keywords: Finance; Financial institutions; Money market